The Influence of Service Quality and Attitude on Customer Satisfaction At PT. PLN (PERSERO) ULP Tais Seluma District - Periantio Periantio; Ida Ayu Made Er Meytha Gayatri; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
Good performance can be seen from the work that can be achieved by an employee. If the results of an The purpose of this study was to determine the effect of service quality and attitude on customer satisfaction at PT. PLN (Persero) ULP Tais Seluma District. The sample in this study was 50 customers at PT. PLN (Persero) ULP Tais Seluma District. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the multiple linear regression equation show a positive regression direction with the equation Y = 2.312 + 0.155X1 + 0.806 X2 + e. This means that if there is an increase in service quality and attitude then customer satisfaction at PT. PLN (Persero) ULP Tais Seluma District will also increase. Service quality has a significant influence on customer satisfaction at PT. PLN (Persero) ULP Tais Seluma District because the value of tcount is greater than ttable (2.227>1.677) and a significance value of 0.031 <0.05. Attitude has a significant influence on customer satisfaction at PT. PLN (Persero) ULP Tais Seluma District because the value of tcount is greater than ttable (8.720>1.677) and a significance value of 0.000 <0.05. Simultaneous test results can be seen that there is a significant influence between service quality and attitudes towards customer satisfaction at PT. PLN (Persero) ULP Tais Seluma District together because the value of Fcount > Ftable (51.284 > 3.20) with a significant value of 0.000 <0.05. The coefficient of determination of R square is 0.686. This means that X1 (service quality) and X2 (attitude) affect customer satisfaction (Y) by 68.6% while the remaining 31.4% is influenced by other variables not examined in this study.